Specifying the diffusion MRI connectome in Chinese-speaking children with developmental dyslexia and auditory processing deficits - Hsiao-Lan Sharon Wang; Natalie Yu-Hsien Wang; Fang-Cheng Yeh (Pediatrics and Neonatology)
Background: Lexical tone identification has a unique role in the perceptual processes of Chinese readers. Reduced lexical tone awareness, along with poor word-decoding abilities, is frequently observed in Chinese-speaking children with developmental dyslexia. However, whether this deficit is linked to reduced auditory processing and interrupted structural connectivity in the brain requires further investigation. This study therefore explores the white matter pathways associated with Chinese character recognition and auditory processing of pitch variations, with the objective of to identify the most representative neural correlates for Chinese developmental dyslexia. Methods: Diffusion magnetic resonance imaging and several behavior measures related to reading attainment and phonological awareness were acquired in twenty-four Chinese-speaking children with developmental dyslexia and twenty-two age-matched controls. We used diffusion magnetic resonance imaging connectometry to explore the relationships between behavior performance and specific white matter tracts. Results: The results revealed significant correlations of the left inferior fronto-occipital fasciculus, cerebellar pathways, and thalamopontine tracts with Chinese character recognition (FDR = 0.03235). In addition, the posterior isthmus and anterior splenium of the corpus callosum correlated with auditory processing (FDR = 0.03980). Conclusion: The study provides evidence that the dysconnectivity on white matter pathways correlated with developmental dyslexia in Chinese-speaking children. Furthermore, the impairments of auditory temporal timing processing presented in poor readers with significant phonological deficits are likely to be a result of impoverished myelinization in sub-cortical tracts. Such findings may assist in the clinical identification of Chinese developmental dyslexia. Keywords: auditory frequency-modulation processing, Chinese developmental dyslexia, connectometry, diffusion MRI, lexical tone awareness